2020
DOI: 10.1108/ijesm-03-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fiscal decentralization on carbon emissions in China

Abstract: Purpose Fiscal fund is the key support of carbon emissions control for local governments. This paper aims to analyze the impact of fiscal decentralization on carbon emissions by spatial Durbin model (SDM), and verify the existence of “free-riding” phenomenon to reveal the behavior of local governments in carbon emissions control. Design/methodology/approach Based on the provincial data of carbon emissions from 2005 to 2016 in China, this paper uses spatial exploratory data analysis technology to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The last point of view is that the relationship between decentralization and IEE is non-linear. Under fiscal decentralization, in order to improve political performance, local governments must not only promote local economic development, but also improve the quality of the local ecological environment (Yang et al 2020). Some scholars have found a nonlinear relationship between decentralization and pollution emissions through research (Cheng et al 2019).…”
Section: Economic Transformation and Ieementioning
confidence: 99%
“…The last point of view is that the relationship between decentralization and IEE is non-linear. Under fiscal decentralization, in order to improve political performance, local governments must not only promote local economic development, but also improve the quality of the local ecological environment (Yang et al 2020). Some scholars have found a nonlinear relationship between decentralization and pollution emissions through research (Cheng et al 2019).…”
Section: Economic Transformation and Ieementioning
confidence: 99%
“…Learning from Li and Wang and Yang et al, industrial structure is measured by the proportion of the secondary industry in the total industrial output. [74,75] Drawing lessons from Liu and Feng and Zhang, technological innovation level is measured by the ratio of R&D expenditure to GDP for each region [64,70]. According to Gani, Zhang, and Zhang, Gross Domestic Product (GDP) is indicated by actual GDP per capita, and population size is indicated by population density of each region [13, 15, 21].…”
Section: Other Variablesmentioning
confidence: 99%
“…2 Literature review and theoretical analysis 2.1 Research into the effect of fiscal decentralization on CO 2 emissions Although academics have begun investigating the carbon dioxide emissions and the impact of fiscal decentralization ( (Matheus et al, 2019;Yang et al, 2020), there is no consensus regarding the impact of fiscal decentralization on carbon dioxide emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it can also result in local governments' (Levinson, 2003). On the other hand, local authorities can bring about economic development while improving environmental quality under fiscal decentralization (Yang et al, 2020). For instance, Hao et al (2020a) found that the impact of fiscal decentralization on CO 2 emissions was negative.…”
Section: Introductionmentioning
confidence: 99%